Performance of an Automatic Variable-Rate Fertilization System Subject to Different Initial Field Water Conditions and Fertilizer Doses in Paddy Fields - Wang, Haiyu; Xu, Junzeng; Chen, Bing; Li, Yawei; Li, Shuai; Liang, Hao; Jiang, Qianjing; He, Yong; Xi, Wenjia (Agronomy (Basel), 2023)
High-performance fertilization equipment with high uniformity is essential for the improvement of fertilizer use efficiency in paddies. The performance of these fertigation systems might be affected by the initial field conditions and fertilizer doses. In this study, the uniformity of fertilization by an automatic system (SF) was investigated; the investigation had two initial field water conditions and fertilizer doses, and manual fertilization by farmers (FF) was used as the control. After fertilization, the Christiansen uniformity coefficient (CU) in the SF paddies was higher than in the FF paddies, and the SF in the non-flooded paddies (SFN) was the highest. With time, the CU of treatments with poor fertilization uniformity was improved; it was driven by the osmotic potential of fertilizer ions, but it was far from exceeding that of the treatments originally conducted with higher CU. For the SF treatments, the fertilizer dose did not affect fertilization uniformity significantly; so, an SF can match the efficient fertilization strategies more precisely. As water-saving irrigation (WSI) is conducive to the production of non-flooded field conditions and the promotion of the efficient use of topdressing, the use of automatic fertilization systems to implement efficient fertilization management practices in WSI paddy fields is suggested.